Genetic divergence in commercial cucumber (Cucumis sativus L.) genotypes - Hasan, Rokib; Hossain, Mohammed Kamal; Alam, Nazmul; Bashar, Abul; Islam, Saidul; Tarafder, Mohammad Jahangir Alam (Bangladesh Journal of Botany, 2018)
Genetic diversity in commercial cucumber genotypes was estimated based on 13 characters. Path analysis revealed that fruits/plant (0.701) and fruit weight (0.379) had maximum positive direct effect on yield. Seven cucumber genotypes were grouped into three different clusters. The highest inter-cluster distance (4.078) was observed between cluster I and II whereas lowest inter-cluster distance (1.011) was observed between the clusters I and III. Cluster II showed highest mean for length of main vine, nodes/plant, primary branches/plant, days to 1st male flowering, length of internodes/plant, fruits/plant and yield/plant whereas cluster III produced highest mean for leaf length, leaf breadth, fruit length, fruit diameter and fruit weight. Cluster II and III contributed 53.85 and 38.46%, respectively towards divergence.